Efek Pemberian Daun Mimba (Azadirachta indica) Terhadap Diameter Hepatosit Tikus (Rattus norvegicus) - Kusuma, Alfana Bagus; Saraswati, Tyas Rini; Sitasiwi, Agung Janika (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Neem leaf (Azadirachta indica) was known as infertility herb. Neem leaf contain of flavonoid compounds which inhibit the damage of cell. This research aimed to examine the effect of neem leaf on hepotocyte and liver lobules diameter. The total of labolatory animals in this research were 12 male Rattus novergicus. This research was conducted by using the Complete Randomized Design (CRD). The animal was treated by neem leaf extracted with 12, 16, and 20 mg/animal/day (PO, P1, P2, P3) respectively. The treatment was treated during 14 days. The liver was made as histological slide by using HE stain with 3-4 Âµ in thickness. The observed parameters were hepatocyte diameter, liver lobules diameter, the final body weight and liver weight. Data here analyzed by ANOVA test. All the analysis were performed with 5% significant level. The results showed that the giving of neem leaf extract had no significant effects (p>0.05) on hepatocyte diameter, liver lobules diameter, liver weight and final body weight. It could be concluded that the giving of ethanolic neem leaves extract with 20 mg/animal/day for 14 days did not affect the hepatocyte diameter, liver diameter, liver weight and final body weight